2004
DOI: 10.1136/jcp.2004.016436
|View full text |Cite
|
Sign up to set email alerts
|

DNA replication regulation protein Mcm7 as a marker of proliferation in prostate cancer

Abstract: Background: Recent studies have shown that minichromosome maintenance (MCM) proteins (Mcm2-7) may be useful proliferation markers in dysplasia and cancer in various tissues. Aims: To investigate the use of Mcm7 as a proliferation marker in 79 lymph node negative prostate cancers and compare it with Ki-67, a commonly used cell proliferation marker. Methods: The percentage of proliferating cells (proliferation index; PI) was calculated for basal and luminal epithelial cells in benign prostate tissue, prostatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
77
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 41 publications
7
77
0
2
Order By: Relevance
“…RLFs, which form the core of the initiation machinery, act as relay stations coupling growth regulatory and DNA damage response pathways to chromosomal replication. We and others have demonstrated that dysregulation of the replication Ki67 Geminin P C 3 -P a r e n t a l P C 3 -e m p t y v e c t o r P C 3 -E R K 5 P C 3 -P a r e n t a l P C 3 -e m p t y v e c t o r initiation machinery is an early event in tumourigenesis and that the Mcm2-7 RLFs are powerful diagnostic and prognostic markers in a wide range of tumour types (Williams et al, 1998Stoeber et al, 1999;Wharton et al, 2001Wharton et al, , 2004Davies et al, 2002;Going et al, 2002;Stoeber et al, 2002;Gonzalez et al, 2003;Kruger et al, 2003;Padmanabhan et al, 2004;Dudderidge et al, 2005;Korkolopoulou et al, 2005;Shetty et al, 2005). Recent reports have shown that the MEK5/ERK5 pathway is implicated in the regulation of cell proliferation, and that increased MEK5/ERK5 signalling results in increased cell proliferation, invasion and metastatic spread during prostate carcinogenesis Mehta et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RLFs, which form the core of the initiation machinery, act as relay stations coupling growth regulatory and DNA damage response pathways to chromosomal replication. We and others have demonstrated that dysregulation of the replication Ki67 Geminin P C 3 -P a r e n t a l P C 3 -e m p t y v e c t o r P C 3 -E R K 5 P C 3 -P a r e n t a l P C 3 -e m p t y v e c t o r initiation machinery is an early event in tumourigenesis and that the Mcm2-7 RLFs are powerful diagnostic and prognostic markers in a wide range of tumour types (Williams et al, 1998Stoeber et al, 1999;Wharton et al, 2001Wharton et al, , 2004Davies et al, 2002;Going et al, 2002;Stoeber et al, 2002;Gonzalez et al, 2003;Kruger et al, 2003;Padmanabhan et al, 2004;Dudderidge et al, 2005;Korkolopoulou et al, 2005;Shetty et al, 2005). Recent reports have shown that the MEK5/ERK5 pathway is implicated in the regulation of cell proliferation, and that increased MEK5/ERK5 signalling results in increased cell proliferation, invasion and metastatic spread during prostate carcinogenesis Mehta et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The constituents of the pre-RC can be regarded as relay stations coupling growth regulatory pathways with DNA replication . We and others have demonstrated in a range of different tumour types that dysregulation of the MCM proteins is an early event in tumourigenesis and have exploited these biomarkers in primary diagnosis, tumour surveillance and prognosis (Williams et al, 1998Stoeber et al, 1999Stoeber et al, , 2002Wharton et al, 2001Wharton et al, , 2004Davies et al, 2002;Going et al, 2002;Gonzalez et al, 2003;Kruger et al, 2003;Padmanabhan et al, 2004;Dudderidge et al, 2005;Korkolopoulou et al, 2005;Shetty et al, 2005). These studies have established that the superior sensitivity of MCM proteins over the standard proliferation marker Ki67 resides in the fact that these biomarkers identify not only cycling cells but also non-cycling cells with proliferative potential ).…”
mentioning
confidence: 99%
“…With the development of (Meng et al, 2001;Padmanabhan et al, 2004) and ovarian serous neoplasms (Scott et al, 2004) chondrosarcoma (Helfenstein et al, 2004), oligodendroglial tumours (Wharton et al, 2001(Wharton et al, , 2004, oesophageal neoplasm (Going et al, 2002), renal cell carcinoma (Dudderidge et al, 2005), breast cancer (Gonzalez et al, 2004), endometrial carcinoma (Li et al, 2005) and thyroid carcinoma (Guida et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of MCM proteins as proliferation markers has been investigated immunohistochemically in several different malignant tumours (Freeman et al, 1999), for example, non-smallcell lung cancer (Ramnath et al, 2001), prostate cancer (Meng et al, 2001;Padmanabhan et al, 2004), oral squamous cell carcinoma (Kodani et al, 2003), chondrosarcoma (Helfenstein et al, 2004), oligodendroglial tumours (Wharton et al, 2001(Wharton et al, , 2004, oesophageal neoplasm (Going et al, 2002), renal cell carcinoma (Dudderidge et al, 2005), breast cancer (Gonzalez et al, 2004), endometrial carcinoma (Li et al, 2005) and thyroid carcinoma (Guida et al, 2005). Most of these studies focused on the detection of MCM2 (Freeman et al, 1999;Chatrath et al, 2003;Davidson et al, 2003;Kodani et al, 2003;Scott et al, 2004).…”
mentioning
confidence: 99%
“…MCM proteins were suggested as potential prognostic markers in a variety of human malignancies, including prostate and breast cancer and bronchial adenocarcinoma (19,(27)(28)(29)(30)(31)(32)(33)(34). Overexpression of Minichromosome maintenance protein 7 (MCM7) was reported to actively contribute to tumor formation, progression and malignant conversion.…”
Section: Introductionmentioning
confidence: 99%